Lysophosphatidic acid decreased macrophage foam cell migration correlated with downregulation of fucosyltransferase 8 via HNF1α. (November 2019) - Chen, Linmu; Zhang, Jun; Yang, Xi; Liu, Yan; Deng, Xiao; Yu, Chao
Abstract: Background and aims: Aberrant fucosylation, such as α-1, 6 fucosylation catalyzed by fucosyltransferase 8 (Fut8), is associated with reduced cell migration and is responsible for cholesterol-enriched foam cell accumulation in the intima in the early stage of atherosclerosis. The current study evaluated the impact of glycosyltransferases on foam cell migration induced by lysophosphatidic acid (LPA) and its potential mechanism. Methods: The mobility of foam cells was evaluated via transwell and scratch assays. The expression of Fut8 and α-1, 6 fucosylation of proteins were assessed by RT-PCR, Western blotting, etc. Overexpression of Fut8 was used to explore the direct relationship between Fut8 and foam cell migration. Dual luciferase reporter assay was performed to determine whether the regulation of Fut8 by LPA occurred at the transcriptional level. Binding of hepatocyte nuclear factor 1-alpha (HNF1α) to the Fut8 promoter was assessed by electrophoretic mobility shift assay and chromatin immunoprecipitation assay. Results: We found that the migration capacity of foam cells induced by LPA was significantly decreased. Fut8 and α-1, 6 fucosylation showed the most obvious decline after treatment with 200 μM LPA for 24 h. Overexpression of Fut8 was able to restore the foam cell migration capacity. Another important finding was that the LPA1 and LPA3 (LPA1, 3 ) receptors were involved in the regulation of Fut8. It is interesting to note that LPA led to a decrease in Fut8 gene transcription activity, and HNF1α transcription factor played a positive role in downregulation of Fut8 promoter activity. Conclusions: Our results strongly indicated that the LPA-LPA1, 3 receptor-HNF1α pathway is involved in the downregulation of Fut8, leading to diminished foam cell migration. Graphical abstract: Image 1 Highlights: Macrophage-derived foam cells induced by LPA have a diminished capacity of migration. Downregulation of Fut8 and α-1, 6-fucosylation levels is involved in the decreased mobility of foam cells. LPA can reduce the combination between HNF1α and Fut8 promoter region by activating its LPA1, 3 receptors.